Relationship between voided volume and the urge to void among patients with lower urinary tract symptoms. (December 2014) - Blaivas, Jerry G.; Tsui, Johnson F.; Amirian, Michael; Ranasinghe, Buddima; Weiss, Jeffrey P.; Haukka, Jari; Tikkinen, Kari A. O.
Abstract Objective.The aim of this study was to explore the relationship between voided volume (VV) and urge to void among patients with lower urinary tract symptoms. Material and methods. Consecutive adult patients (aged 23–90 years) were enrolled, and completed a 24 h bladder diary and the Urgency Perception Scale (UPS). Patients were categorized as urgency or non-urgency based on the Overactive Bladder Symptom Score. The relationship between UPS and VV (based on the bladder diary) was analyzed by Spearman's rho and proportional odds model. Results. In total, 1265 micturitions were evaluated in 117 individuals (41 men, 76 women; 56 individuals in the urgency and 61 in the non-urgency group). The mean (± SD) VV and UPS were 192 ± 127 ml and 2.4 ± 1.2 ml in the urgency group and 173 ± 124 ml and 1.7 ± 1.1 ml in the non-urgency group, respectively. Spearman's rho (between UPS and VV) was 0.21 [95% confidence interval (CI) 0.13–029, p < 0.001] for the urgency group, 0.32 (95% CI 0.25–0.39, p < 0.001) for the non-urgency group, and 0.28 (95% CI 0.23–0.33, p < 0.001) for the total cohort. Urgency patients had higher UPS [odds ratio (OR) 3.1, 95% CI 2.5–3.8]. Overall, each additional 50 ml VV increased the odds of having a higher UPS with OR 1.2 (95% CI 1.2–1.3). The relationship between VV and UPS score was similar in both groups (p = 0.548 for interaction). Conclusion. Although urgency patients void with a higher UPS score, among both urgency and non-urgency patients there is only a weak correlation between VV and the urge to void. This suggests that there are factors other than VV that cause the urge to void.